Effects of Soil Nutrient Heterogeneity on the Growth and Invasion Success of Alien Plants: A Multi-Species Study - Gao, Fang-Lei; He, Qiao-Sheng; Zhang, Yi-Dan; Hou, Jia-Hui; Yu, Fei-Hai (Frontiers in Ecology and Evolution, 2021)
Spatial heterogeneity in soil nutrient availability can influence performance of invasive plant species under competition-free environments. However, little was known about whether invasive plants perform better under heterogeneous than under homogeneous soil nutrient conditions in competition with native plant communities. We conducted a multi-species greenhouse experiment to test the effect of soil nutrient heterogeneity on the growth and invasion success of alien plants in a native plant community. We grew 10 alien invasive plant species that are common in China under a homogeneous or heterogeneous environment alone or together with a community consisting of six native plant species from China. Compared with the homogeneous soil condition, the heterogeneous soil condition significantly increased aboveground biomass of the invasive plants. However, soil nutrient heterogeneity did not affect the relative abundance of the invasive species, as measured by the ratio of aboveground biomass of the invasive species to total aboveground biomass of the whole community (invasive and native species together). There were no significant interactive effects of soil nutrient heterogeneity and competition from the native community on aboveground biomass of the alien invasive plants or its relative abundance. Our results indicate that soil nutrient heterogeneity has a positive effect on the growth of invasive plants in general, but do not support the idea that soil nutrient heterogeneity favors the invasion success of exotic plant species in native plant communities.